Estimasi Serapan dan Nilai Ekonomi Karbon Rhizophora apiculata di Kawasan Konservasi Perairan Nias Utara: Carbon Sequestration Estimation and Economic Valuation of Rhizophora apiculata in the North Nias Marine Conservation Area (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2025)
Mangrove ecosystems are categorized as blue carbon due to their ability to store atmospheric carbon. Rhizophora apiculata, the dominant mangrove species in the Sawo-Lahewa conservation area, North Nias Regency, plays a key role in carbon sequestration and is widely used in ecosystem rehabilitation. This study aims to estimate the carbon stock and its economic value under different compensation scenarios. A non-destructive method was applied to estimate biomass using allometric equations, followed by calculations of carbon stock and CO₂ absorption. The economic value was assessed using three approaches: Forest Carbon Partnership Facility (FCPF), the U.S. government's Social Cost of Carbon (SCC), and Indonesia’s domestic market under the HPP Law. The estimated carbon stock of R. apiculata is 3,687.78 tons/ha, equivalent to 13,534.15 tons of CO₂ absorbed. In 2023, its economic value is approximately IDR 989.35 million (FCPF), IDR 8.31 billion (SCC), and IDR 406.02 million (domestic market). Projected values in 2043 increase to IDR 2.17 billion, IDR 18.21 billion, and IDR 889.65 million, respectively. These results highlight the ecological and economic importance of R. apiculata in supporting climate regulation services. Strategic conservation and sustainable management of mangroves can enhance their carbon offset potential, contributing to both environmental and economic benefits.